2017
DOI: 10.31018/jans.v9i2.1266
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly management of Sitophilus oryzae and Rhyzoper thadominica in stored wheat at Pantnagar, Uttarakhand

Abstract: he laboratory experiments were conducted to study the efficacy of some indigenous products such as plant products (chopped neem leaves ajwain seed powder, garlic capsules, saw dust), animal derivedproducts ( cow dung cake powder, cow urine) and inert materials ( ash powder, sand, talcum powder, salt) @ 2g/100g of wheat grains against rice weevil, Sitophilus oryzae (Linn.) and lesser grain borer, Rhyzoper thadominica (Fab.) on stored wheat by undertaking various parameters viz., percent adult emergence, percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Talc recorded inefficient results for the protection of the stored bean seeds against bean weevil Acanthoscelides obtectus, the population of the pest recovering after 50 days from treatment, the same as in control variant by. On the other hand, Yadav and Tiwari (2017) found that the inert materials such as talc powder was effective against adult emergence, reduced damage and weight loss of Sitophilus oryzae and Rhyzopertha dominica on treated wheat grains.…”
Section: Discussionmentioning
confidence: 99%
“…Talc recorded inefficient results for the protection of the stored bean seeds against bean weevil Acanthoscelides obtectus, the population of the pest recovering after 50 days from treatment, the same as in control variant by. On the other hand, Yadav and Tiwari (2017) found that the inert materials such as talc powder was effective against adult emergence, reduced damage and weight loss of Sitophilus oryzae and Rhyzopertha dominica on treated wheat grains.…”
Section: Discussionmentioning
confidence: 99%
“…Here the inert material treatment of saw dust reported the highest adult emergence of T. castaneum was 40.67 per cent, followed by the next treatments are paddy straw (31.67%) and paddy husk ash (25.33%). Yadav and Tiwari (2017) reported that minimum adult emergence in ash powder, sand and cow dung ash was 2.00, 2.33 and 8.33 per cent. By way of usual the untreated control noticed the maximum number of adult emergences 76 per cent after 90 DAT and the least number of adult emergences was observed in the treatment of boric acid (12.67%).…”
Section: Evaluation Of Adult Emergencementioning
confidence: 99%